2012
DOI: 10.2147/ce.s33430
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based review of linezolid for the treatment of methicillin-resistant Staphylococcus aureus (MRSA): place in therapy

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA), including community-associated and hospital-associated strains, is a major cause of human morbidity and mortality. Treatment options have become limited due to the emergence of MRSA strains with decreased sensitivity to vancomycin, which has long been the first-line therapy for serious infections. This has prompted the search for novel antibiotics that are efficacious against MRSA. Linezolid, an oxazolidinone class of antibiotic, was approved by the Food and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 102 publications
1
29
0
11
Order By: Relevance
“…14 FDA-approved the drug linezolid to treat the following conditions: (1) vancomycin-resistant Enterococcus faecium infections, including cases with concurrent bacteraemia; (2) nosocomial pneumonia caused by S. aureus, including methicillin-susceptible (MSSA) andresistant strains, or Streptococcus pneumoniae (including multidrug-resistant strains); (3) complicated skin and skin-structure infections, including diabetic foot infections (DFIs), without concomitant osteomyelitis, caused by S. aureus (MSSA and MRSA), Streptococcus pyogenes, or Streptococcus agalactiae; (4) uncomplicated skin and skin-structure infections caused by MSSA or S. pyogenes; (5) community-acquired pneumonia caused by S. pneumoniae, including cases with concurrent bacteremia, or MRSA. 15 One study reported that the incidence of linezolid associated thrombocytopenia was higher in patients with renal dysfunction than those with normal renal fuction. 16 Another study showed though there is good clinical outcome but high rate of adverse reactions during linezolid therapy for serious infections and they also proposed a protocol for monitoring therapy in complex patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 FDA-approved the drug linezolid to treat the following conditions: (1) vancomycin-resistant Enterococcus faecium infections, including cases with concurrent bacteraemia; (2) nosocomial pneumonia caused by S. aureus, including methicillin-susceptible (MSSA) andresistant strains, or Streptococcus pneumoniae (including multidrug-resistant strains); (3) complicated skin and skin-structure infections, including diabetic foot infections (DFIs), without concomitant osteomyelitis, caused by S. aureus (MSSA and MRSA), Streptococcus pyogenes, or Streptococcus agalactiae; (4) uncomplicated skin and skin-structure infections caused by MSSA or S. pyogenes; (5) community-acquired pneumonia caused by S. pneumoniae, including cases with concurrent bacteremia, or MRSA. 15 One study reported that the incidence of linezolid associated thrombocytopenia was higher in patients with renal dysfunction than those with normal renal fuction. 16 Another study showed though there is good clinical outcome but high rate of adverse reactions during linezolid therapy for serious infections and they also proposed a protocol for monitoring therapy in complex patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The FDA has approved linezolid therapy in the year 2000 and it can be used safely for 28 days, beyond this may lead to high plasma concentration and an increased risk of non-negligible toxicities. 4,5 As a consequence, increased drug concentrations could represent a risk factor for severe toxic effects against target organs (e.g. brain, optic nerve, kidney, skeletal muscular tissue) leading to increased risk of severe adverse reactions mainly thrombocytopenia, myelosuppression and peripheral neuropathy.…”
mentioning
confidence: 99%
“…drug administration, keeping the patient out of hospital or enabling earlier discharge [5]. It is recommended for MRSA infections, as an initial or alternative therapy for the following conditions: SSTI [5,4], DFI [24], pneumonia, osteomyelitis, septic arthritis, meningitis, brain abscess, subdural empyema, spinal epidural abscess and septic thrombosis of the cavernous or dural venous sinus [25][26][27], the latter based on the excellent CNS concentrations achieved [26]. Linezolid also may reduce toxin production in pneumonia, although whether this improves clinical outcomes is not yet clear [26,27].…”
Section: Oxazolidinonesmentioning
confidence: 99%
“…En series clínicas o estudios comparativos no randomizados que involucran pacientes con osteomielitis, linezolid ha demostrado tasas de curación entre 55 y 100% [20][21][22][23] , valores similares a los obtenidos con cotrimoxazol 3,8,9 . Sin embargo, linezolid es un compuesto caro y se asocia a un riesgo de anemia, trombocitopenia, polineuropatía, neuritis óptica o acidosis láctica cuando se usa por perío-dos prolongados 21,22,[24][25][26] . Además, puede inducir toxicidad serotoninérgica cuando se aplica con inhibidores de la recaptación de serotonina 25 .…”
Section: Artículo Originalunclassified
“…Sin embargo, linezolid es un compuesto caro y se asocia a un riesgo de anemia, trombocitopenia, polineuropatía, neuritis óptica o acidosis láctica cuando se usa por perío-dos prolongados 21,22,[24][25][26] . Además, puede inducir toxicidad serotoninérgica cuando se aplica con inhibidores de la recaptación de serotonina 25 . Considerando su eficacia comparativa, en un estudio controlado randomizado, cotrimoxazol-rifampicina demostró ser equivalente a linezolid-rifampicina en pacientes con infecciones óseas o articulares, aunque el número de casos con osteomielitis fue pequeño 8 .…”
Section: Artículo Originalunclassified